A recombined skin composed of human keratinocytes cultured on cell-free pig dermis - Matousková, E; Vogtová, D; Königová, R (Burns, 1993)
Treatment of full skin thickness burns requires replacement of both the dermal and the epidermal components of the skin. We describe a method of preparing recombined human/pig skin (RHPS) by cultivating human keratinocytes on dried cell-free pig dermis (CFPD). CFPD dried on a tissue culture dish forms a thin collagen film which behaves like a firm substrate for cell cultures. HK were grown on the epidermal side of the CFPD using lethally irradiated 3T3 cells as feeders. After reaching confluency of human keratinocytes, human fibroblasts can be cultured on the dermal side of the RHPS. It was possible to obtain approximately 500 cm2 of the RHPS from 1 cm2 human split-skin graft in 3 weeks. RHPS is easy to handle, is similar in structural, mechanical and adhesive properties to the normal skin, and can be meshed. This RHPS might be advantageous for permanent covering of wounds in major burns.
Keywords: Cells, Cultured; kultivované buňky; buněčné dělení; biologické krytí; prasata; keratinocyty; Biological Dressings; Swine; zvířata; Cell Division; Humans; Keratinocytes; Fibroblasts; Skin; kůže; lidé; fibroblasty; Animals